Delayed chest wall hematoma caused by progressive displacement of rib fractures after blunt trauma. (June 2016) - Sato, Nobuhiro; Sekiguchi, Hiroshi; Hirose, Yasuo; Yoshida, Satoru
Abstract: Rib fracture is a common injury resulting from blunt thoracic trauma. Although hemothorax and pneumothorax are known delayed complications of rib fracture, delayed chest wall hematoma has rarely been reported. We discuss the case of an 81-year-old woman who was not undergoing antiplatelet or anticoagulant therapy who presented to our emergency department after a traffic injury. This patient had a nondisplaced rib fracture that went undetected on the initial computed tomography scan; the development of progressive displacement led to hemorrhagic shock due to delayed chest wall hematoma. The chest wall hematoma was effectively diagnosed and treated via contrast-enhanced computed tomography and angiographic embolization. This case highlights the possibility of this potential delayed complication from a common injury such as a rib fracture.